2015
DOI: 10.1353/cpr.2015.0045
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Community-Based Tailored Exercise Program for People With Severe and Persistent Mental Illness

Abstract: Background People with severe and persistent mental illness (SPMI) are at a greater risk of medical issues compared with the general population. Exercise has a positive effect on physical and mental health outcomes among this population in community settings. Objectives To describe community-based participatory research (CBPR) methods used to tailor an exercise program among people with SPMI, demonstrate its impact, and present lessons learned for future research. Methods The partnership developed a projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Yet poor uptake of PA by this population remains a problem [ 7 , 8 ]. Poor recruitment to PA interventions is often reported [ 20 ], with patients citing numerous physical health, psychological and socio-ecological barriers to PA [ 11 – 13 ]. Non-uptake of PA by people with SMI does not necessarily reflect a lack of motivation or intention to be active; Ussher et al [ 12 ] found a high level of interest in PA among people with SMI, but low levels of activity.…”
Section: Introductionmentioning
confidence: 99%
“…Yet poor uptake of PA by this population remains a problem [ 7 , 8 ]. Poor recruitment to PA interventions is often reported [ 20 ], with patients citing numerous physical health, psychological and socio-ecological barriers to PA [ 11 – 13 ]. Non-uptake of PA by people with SMI does not necessarily reflect a lack of motivation or intention to be active; Ussher et al [ 12 ] found a high level of interest in PA among people with SMI, but low levels of activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that interventions that include physical activity or education regarding healthy lifestyle are a cost‐efficient way to improve health among persons with SMI . However, many persons with SMI are affected by cognitive impairments, making it particularly difficult to be motivated for the implementation of healthy lifestyle habits .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that interventions that include physical activity or education regarding healthy lifestyle are a costefficient way to improve health among persons with SMI. 23,[55][56][57] However, many persons with SMI are affected by cognitive impairments, making it particularly difficult to be motivated for the implementation of healthy lifestyle habits. 10 In contrast to many other lifestyle programs, the present intervention included education on strategies to counteract the possible problems of mental illness that may hinder lifestyle changes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that SS in the general population critically influences the participation of individuals in physical activity (Draper, Grobler, Micklesfield, & Norris, ; Mendonça & Farias Júnior, ; Zhang et al., ). Other studies have also indicated the importance of social interaction in promoting physical activity in those with SMDs (Gray et al., ; Hoffmann et al., ). SS can come from several different groups, such as family and friends, in various forms, for example, emotional and financial help.…”
Section: Introductionmentioning
confidence: 95%